Performance evaluation of the soft soil reinforced ground palm oil fuel ash layer composite - Mujah, D.; Rahman, Muhammad; Zain, N. (2015)
© 2015 Elsevier Ltd. All rights reserved. This study seeks to validate the possible reuse of the ground palm oil fuel ash (POFA) in soft soil improvement. POFA used in the present study was derived from the abundantly available palm oil waste residues from the nearby palm oil mill. Once the POFA is dried, it is further grounded to two different particle sizes i.e. 30 µm (large particle) and 12 µm sieve (small particle) in order to determine the effect of the POFA fineness in soft soil improvement. Furthermore, a one dimensional deformation analysis was carried out using the oedometer apparatus to investigate the effect of water saturation in soft soil samples incorporating both the original unground POFA. The result showed that the improvement factor portrayed by the smaller particle size of the ground POFA was much more pronounced as compared to the larger particle size. Similar trend was found in the consolidation results especially when the soft soil sample was fully saturated. Also, the shear strength parameters of the reinforced soft soil with ground POFA increased significantly at about 50%-60% for both the internal friction angle and the cohesion values.